2013
DOI: 10.1111/jpn.12115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of using black seed (Nigella sativa), cumin seed (Cuminum cyminum), probiotic or prebiotic on growth performance, blood haematology and serum biochemistry of broiler chicks

Abstract: A 42-day trial was conducted to compare the effects of the following seven experimental diets, which varied in black seed, cumin seed, probiotic or prebiotic concentrations, on the broiler chicks: control (no additives), diet BS1 (4 g/kg black seed), diet BS2 (8 g/kg black seed), diet CS1 (4 g/kg cumin seed), diet CS2 (8 g/kg cumin seed), diet Pro (1 g/kg probiotic Primalac(®)) and diet Pre (2 g/kg prebiotic Fermacto(®)). A total of 420 1-day-old male broiler chicks, initially weighing an average of 43 g, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
7
21
0
Order By: Relevance
“…There were no changes in H/L ratio in response to the experimental diets in our study, meaning that the additives had no impact on the stress level of quails. These results are in accordance with the study of Alimohamadi, Taherpour, Ghasemi, and Fatahnia (), who reported that adding prebiotics and probiotics to broiler diets did not alter the H/L ratio.…”
Section: Discussionsupporting
confidence: 93%
“…There were no changes in H/L ratio in response to the experimental diets in our study, meaning that the additives had no impact on the stress level of quails. These results are in accordance with the study of Alimohamadi, Taherpour, Ghasemi, and Fatahnia (), who reported that adding prebiotics and probiotics to broiler diets did not alter the H/L ratio.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the improvements were of similar magnitude to the ones determined for treatment VM containing virginiamycin, known as a well-documented AGP in broiler diets (Rostami et al 2015). Similar to the finding of the current study, an improvement in FCR in broilers when fed herbal supplements comes as a result of higher BWG at a largely unchanged feed intake (Alimohamadi et al 2014;Ghasemi et al 2014;Omidi et al 2015). AV constituents (anthraquinones and pyrocatechol) have antimicrobial and antiviral activity against a wide range of pathogens (Yun et al 2009;Radha & Laxmipriya 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the finding of the current study, an improvement in FCR in broilers when fed herbal supplements comes as a result of higher BWG at a largely unchanged feed intake (Alimohamadi et al . ; Ghasemi et al . ; Omidi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant compound in N. sativa is TQ that possesses antioxidant, anti-inflammatory, and antiobesity properties; it was also revealed that N. sativa decreases LDL, total cholesterol, and TG levels. [10111213] In 2013, Ahmad S. et al . showed that treatment with TQ decreased the lipid peroxidation marker, MDA in the serum, and increased the TAC of the plasma to a normal level.…”
Section: Discussionmentioning
confidence: 99%
“…The major compound in N. sativa is thymoquinone (TQ), having anti-inflammatory, antioxidant, and antiobesity effects. [510111213] Because of the high prevalence of obesity and its side effects, as well as people's inclination to lose weight without using chemical drugs, utilization of herbal plants can be beneficial. The purpose of this study is to evaluate the effects of TQ, hydroalcoholic, and hexane extracts of N. sativa on the lipid profile, serum antioxidant capacity, and UCP-1 gene expression in the BAT of mice.…”
Section: Introductionmentioning
confidence: 99%